2022
DOI: 10.3390/membranes12030293
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risk Evaluation and Removal of Emerging Pollutants in Urban Wastewater by a Hollow Fiber Forward Osmosis Membrane

Abstract: Forward osmosis (FO) is a promising technology for the treatment of urban wastewater. FO can produce high-quality effluents and preconcentrate urban wastewater for subsequent anaerobic treatment. This membrane technology makes it possible to eliminate the pollutants present in urban wastewater, which can cause adverse effects in the ecosystem even at low concentrations. In this study, a 0.6 m2 hollow fiber aquaporin forward osmosis membrane was used for the treatment of urban wastewater from the Valladolid was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…In total, 80.22% is recovered. In other similar studies of FO, they found losses between 10 and 20% of organic matter in FO processes due to the adsorption of organic matter on the membrane, as mentioned above [ 21 , 27 , 30 , 32 ]. This loss of organic matter by the LPRO processes, which has not been found in the literature, could be a consequence of the fact that in LPRO, there is greater fouling of the membrane and part of the organic matter remains adsorbed on the membrane matrix, as discussed in Section 3.3 .…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…In total, 80.22% is recovered. In other similar studies of FO, they found losses between 10 and 20% of organic matter in FO processes due to the adsorption of organic matter on the membrane, as mentioned above [ 21 , 27 , 30 , 32 ]. This loss of organic matter by the LPRO processes, which has not been found in the literature, could be a consequence of the fact that in LPRO, there is greater fouling of the membrane and part of the organic matter remains adsorbed on the membrane matrix, as discussed in Section 3.3 .…”
Section: Resultsmentioning
confidence: 68%
“…Other studies report losses in organic matter that may be because part of the organic matter remains adsorbed on the active surface of the membrane [ 21 , 27 , 30 , 32 ]. This does not occur in this work, because a stabilization stage is carried out and, therefore, we start from a TOC value that already has considered the possible concentration adsorbed on the membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium chloride (VWR chemicals, Belgium), at concentrations of 30 g·L −1 and 200 g·L −1 , was used for the DS. Both salt concentrations were selected because in other studies [ 26 ], they led to high permeate fluxes and low reverse salt fluxes. As for the 30 g·L −1 of NaCl concentration, this was selected based on the characterization of an actual brine obtained from the table olive producing industry [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FO technology is able to recover up to 85% of PW and operate with a feed reaching as high as 150,000 mg/L of TDS concentrations. Hence, FO processes are more reliable in PW treatment as compared to the RO process [ 25 , 26 , 27 ]. Although FO membranes exhibit less fouling than the membrane technologies utilizing pressure, their impact is nevertheless substantial [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%